2022
DOI: 10.3390/ijerph19116734
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Broadband Infrastructure on Carbon Emission Efficiency of Resource-Based Cities in China: A Quasi-Natural Experiment from the “Broadband China” Pilot Policy

Abstract: Resource-based cities (RBCs) face serious environmental pollution, and there are efforts to try to overcome those challenges by transforming industrial structure through investing in new technologies. Based on the panel data of 114 prefecture-level resource-based cities in China, this paper uses the difference-in-differences (DID) method to identify the effects of the “Broadband China” pilot policy on the carbon emission efficiency of resource-based cities. The results show that the “Broadband China” pilot pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Carbon emission intensity is defined as the amount of carbon dioxide emissions per unit of GDP, which is directly related to environmental losses [ 61 ]. Some studies suggest that an increase in Internet penetration rate can improve environmental quality by reducing greenhouse gas emissions [ 31 , 32 ].…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon emission intensity is defined as the amount of carbon dioxide emissions per unit of GDP, which is directly related to environmental losses [ 61 ]. Some studies suggest that an increase in Internet penetration rate can improve environmental quality by reducing greenhouse gas emissions [ 31 , 32 ].…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…Due to the differences in administrative level, urban scale, and urban resources, “Broadband China” pilot policy may have heterogeneous effects on urban green development. Hence, to further assess the impact of city differences on green development, we refer to Li et al (2022) and set city dummy variables in terms of city class, city size, and city resources, and substitute the interaction term between the dummy variables and the “Broadband China” pilot policy variables into the regression [ 61 ]. (1) Municipalities directly under the central government, provincial capitals, and sub-provincial cities are classified as central cities, assigned the value of 1, and the remaining cities are classified as peripheral cities, assigned the value of 0.…”
Section: Further Analysismentioning
confidence: 99%
“…Meanwhile, Hou et al [22] found that due to the locking effect of technological innovation and human capital, the substitution of industries and technologies in RBCs requires huge investment, leading to low carbon production efficiency. Additionally, scholars have discussed the impact on CO 2 emissions from various points of view, such as urbanization, broadband infrastructure, technological innovation, resource utilization and the green finance of RBCs [31][32][33][34]. However, research on the effect of environmental regulations on the CEE of RBCs is comparatively lacking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, some literature has used quasi-natural experiments to assess various effects of the DE. In particular, for "BC" demonstration cities, which are the focus of this paper, there are rich discussions in the existing literature, including the economic effects, technological effects, and industrial structure effects of "BC" demonstration cities [14][15][16][17]. For example, Zhang et al (2022) examined the exogenous impact of broadband Internet infrastructure on business productiveness by using the implementation of "BC" strategy as an exogenous shock [18], and Zou and Pan (2022) used "BC" as a quasi-natural experiment to elucidate the effect of network construction on environmental pollution reduction using the double-difference method [9].…”
Section: Theoretical Mechanisms and Research Hypothesesmentioning
confidence: 99%
“…Resource-based cities have a higher dependence on energy due to their industrial base. Although the widespread application of digital technology can alleviate regional environmental pressure, there is inertia in economic development, which to some extent makes it difficult to change the "brown" development model; therefore, the impact of the DE on carbon emission performance cannot be highlighted in resource-based cities [16,17]. The resource-dependent economic development model also has a differential impact on regional carbon emissions, with city size showing a positive correlation with regional economic growth to a certain extent, while China's economic activities have distinct regional characteristics, with significant differences in location advantages, resource endowments, ecological environment, and ethnic and cultural dimensions in different regions.…”
Section: Theoretical Mechanisms and Research Hypothesesmentioning
confidence: 99%